Acute sonographic changes in common carotid artery after NESA neuromodulation intervention in healthy adults: a randomized controlled clinical trial - Mínguez-Esteban, Isabel; De la Cueva-Reguera, Mónica; Abuín-Porras, Vanesa; Romero-Morales, Carlos; Almazán-Polo, Jaime; Bravo-Aguilar, María (Frontiers in Neuroscience, 2025)
IntroductionThe endothelium plays a key role in vascular health, and its dysfunction is a major risk factor for cardiovascular diseases (CVD). Non-invasive neuromodulation techniques, such as NESA, aim to improve vascular tone and function by targeting the autonomic nervous system. However, evidence regarding their acute vascular effects is still limited.MethodsA randomized controlled trial was conducted with 40 participants divided into NESA (n = 20) and placebo (n = 20) groups. Both groups underwent 20-min interventions. Sonographic assessments of the left CCA, including lumen diameter (LD), intima-media thickness (IMT), and peak systolic velocity (PSV), along with blood pressure (BP) and heart rate (HR), were performed before and immediately after the intervention.ResultsSignificant increases in LD and cross-sectional area (CSA) were observed in the NESA group compared to placebo (p < 0.001), alongside a decrease in IMT (p < 0.05). HR showed a significant reduction post-intervention in both groups, with a more pronounced effect in the NESA group (p = 0.001). No significant changes were found in BP or PSV.DiscussionThe findings demonstrate that NESA neuromodulation induces immediate changes in vascular parameters, including increased LD and CSA and decreased IMT. These results highlight measurable acute vascular effects in healthy individuals following NESA intervention.